2014
DOI: 10.1155/2014/580626
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Intraperitoneal Administration of Quercetin Decreased Lymphocyte DNA Damage and Plasma Lipid Peroxidation Induced by TSA In Vivo

Abstract: Our previous study showed that quercetin enhances the anticancer effect of trichostatin A (TSA) in xenograft mice given quercetin intraperitoneally (10 mg/kg, 3 times/week). Herein, we investigate whether quercetin administered orally exerts such an effect and prevents the cytotoxic side effects of TSA. We found that quercetin given orally (20 and 100 mg/kg, 3 times/week) failed to enhance the antitumor effect of TSA although it increased the total quercetin concentration more than quercetin administered intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Other studies showed that oral administration of quercetin or hesperidin mainly increased plasma concentrations of their metabolites (e.g. Q3G and hesperetin) (Chan et al, 2014;Ting, Yeh, & Lien, 2011;Yamamoto et al, 2013). In addition, studies have also found that the amounts of metabolites recovered were significantly less than the amounts of flavonoid ingested (Erlund et al, 2001;.…”
Section: Optimization Of Non-toxic Flavonoid Concentrationsmentioning
confidence: 97%
“…Other studies showed that oral administration of quercetin or hesperidin mainly increased plasma concentrations of their metabolites (e.g. Q3G and hesperetin) (Chan et al, 2014;Ting, Yeh, & Lien, 2011;Yamamoto et al, 2013). In addition, studies have also found that the amounts of metabolites recovered were significantly less than the amounts of flavonoid ingested (Erlund et al, 2001;.…”
Section: Optimization Of Non-toxic Flavonoid Concentrationsmentioning
confidence: 97%
“…Many pharmacological studies show that intraperitoneal route is preferred because it favours a better absorption of active principles (Chan et al., ). In addition, the absorption and metabolism of these through the gastrointestinal tract can affect their concentrations and structures in vivo (Memmott et al., ; Sharma, Gescher, & Steward, ).…”
Section: Discussionmentioning
confidence: 99%
“…The purity of all of the chemical reagents was not less than analytical grade. The dose concentration selection for quercetin and ketamine was based on the literature [28][29][30][31].…”
Section: Chemical Reagents and Drugsmentioning
confidence: 99%
“…After one week of adaptation, the mice were randomly divided into five groups (n = 8 in each group): Corn oil + Saline, Quercetin 50 + Saline, Corn oil + Ketamine, Quercetin 25 + Ketamine and Quercetin 50 + Ketamine. A ketamine injection was applied in physiological saline at 1 ml/100 g volume [32,33] and oral administration of quercetin was applied in corn oil at 1 ml/100 g volume [29,31]. Corn oil and quercetin (25 or 50 mg/kg/day) were given by orogastric gavage once a day for 21 days.…”
Section: Animals and Experimental Designmentioning
confidence: 99%